Japanese Translation and Validation of the Environmental Assessment Tool–Higher Care. (October 2021) - Brennan, Sumiyo; Doan, Therese; Bennett, Kirsty; Hashimoto, Yumiko; Fleming, Richard
Objective: The purpose of this study was to translate the Environmental Assessment Tool–Higher Care (EAT-HC) into Japanese and validate its use in small-scale group living facilities in Japan. Background: Environment of a facility is shown to improve its residents' quality of life (QOL). Japan's "welfare-based nursing homes for the elderly" are gradually shifting to a small-scale group living concept called group care units (GCUs). However, there is no appropriate environmental tool available for evaluating GCUs. The application of valid environmental assessment tools brings about a better understanding of the nature of good environments and the relationship between environments and outcomes for residents living with dementia. Methods: The study had a mixed method design conducted in several steps, covering translation and adaptation. The translation phase involved (1) forward translation and (2) backward translation. The adaptation phase involved (3) content validity and homogeneity reliability and (4) concurrent validity and interrater reliability. Results: 71 Items (92%) met the acceptable level of content validity (item-content validity index [CVI] > .79) and had good scale-CVI of .88. Concurrent validity was confirmed between .65 and .78 ( p < .001). For reliability test, the internal consistency of six subscales was between .88 and .98. Overall interobserver agreement was 90.3%. Intraclass correlation coefficients were .80–.98 ( p < .001), and homogeneity reliability coefficient for all items was >.76 ( p < .01). Conclusions: Validation of the EAT-HC-Japanese Version (EAT-HC-JV) was confirmed as an appropriate tool for environmental assessment to enhance the QOL in Japan's GCUs. For future study, we plan to modify the EAT-HC-JV to adapt to Japanese cultural aspects in order to increase its usability in Japan.